A review on food allergy: pathogenesis, diagnosis methods and treatment approaches - Desai, Muskaan V.; Sachdeva, Punam D. (International Journal of Basic & Clinical Pharmacology, 2023)
An exaggerated immune reaction to a food that takes place in a vulnerable host is referred to as a food allergy. The two main types of food-induced allergy diseases are those caused by Immunoglobulin E (IgE) antibodies and those caused by non-IgE-mediated mechanisms. These reactions are frequently brought on by food allergens such as egg, seafood, fruits, milk, soy, peanut, etc. In India, roughly 26.5% of the population has been impacted by food-induced allergy diseases. Age, sex, heredity, and geographic location of the patient, as well as vitamin D deficiency and other allergic reactions, are risk factors that might result in life-threatening food allergies. Skin prick test, oral food challenge, component resolved diagnostic testing are the most widely used diagnostic tests for food allergy. Pharmacotherapy of food induced allergic reactions include epinephrine therapy and use of antihistamine drugs. However, the main stay of treatment is avoidance of responsible food and food desensitization. Some home remedies can also be used in order to control allergic reactions caused by food allergens. All these remedies directly or indirectly improve the health of immune system to prevent food induced allergic reactions. The objective of this study was to throw a light on the pathogenesis, diagnostic methods and possible treatment options for food allergy.